2013
DOI: 10.1194/jlr.m030700
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary saturated fat content on adiposity, macrophage behavior, inflammation, and metabolism: composition matters

Abstract: We examined the effects of three high‐fat diets differing in the percentage of total calories from saturated fat (SF) (6%, 12%, and 24%), but identical in total fat (40%), on body composition, macrophage behavior, inflammation, and metabolic dysfunction in mice. Diets were administered for 16 weeks. Body composition and metabolism (glucose, insulin, triglycerides, LDL‐C, HDL‐C, total cholesterol) were examined monthly. Adipose tissue (AT) expression of marker genes for M1 and M2 macrophages and inflammatory me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 64 publications
(70 reference statements)
6
113
2
4
Order By: Relevance
“…Initiation of the inflammatory process comes from cellular stress at the level of the adipocyte [56]. Adipocytes undergo hyperplasia and hypertrophy, and together with circulating free fatty acids and their by-products, initiate an inflammatory signaling cascade.…”
Section: Obesity Systemic Inflammation and Low Back Painmentioning
confidence: 99%
“…Initiation of the inflammatory process comes from cellular stress at the level of the adipocyte [56]. Adipocytes undergo hyperplasia and hypertrophy, and together with circulating free fatty acids and their by-products, initiate an inflammatory signaling cascade.…”
Section: Obesity Systemic Inflammation and Low Back Painmentioning
confidence: 99%
“…Lifestyle factors such as diet and nutritional status, physical activity and stress can influence the ability to mount effective immune responses to infectious challenge (Lesourd, 2006). In particular, immunocompetence is directly affected by nutrition as deficiencies in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 several vitamins and minerals, protein-energy malnutrition and excessive intakes of saturated fatty acids can impair immune responses (Enos et al, 2013;Lesourd, 2006;Pae et al, 2012).…”
Section: Dietary Influence On the Aged Immune Response (Improvement/rmentioning
confidence: 99%
“…However, most studies, including our own, have found that inflammatory changes in the visceral adipose tissue are mirrored by similar changes in subcutaneous adipose tissue [23]. In addition, the intake and energy expenditure of the patients studied was partly unknown and may have affected the degree of overweight and adipose tissue inflammation [24,25].…”
Section: Discussionmentioning
confidence: 99%